Comparative studies of remotely sensed coastline mapping techniques / Siti Aekbal Salleh, Nurhanis Syazlia Hasshim and Nor Aizam Adnan - Salleh, Siti Aekbal; Hasshim, Nurhanis Syazlia; Adnan, Nor Aizam (Faculty of Architecture, Planning & Surveying, 2015)
The shoreline is always changing its shape and position dynamically. There are many remote sensing techniques can be used to depict coastline. Band Ratio, Tasselled Cap Transformation, ISODATA and NDWI are amongst the established technique use to map coastline. A comparison is needed to identify which of these techniques is offer better accuracy. Thus, the aim of this study is to identify the optimum method for mapping coastline. In order to achieve this aim, the objectives of this project are: i) to study technique of coastline extraction using remote sensing image, ii) to map coastline using the selected remote sensing technique for comparison and iii) to determine accuracy these techniques by using local authority data as the baseline. The study area for this research is at Pantai Puteri, Tanjung Keling, Melaka. The techniques explored in this study are Band ratio, Tasseled Cap Transformation, Unsupervised Classification (ISODATA) and Normalized Difference Water Index (NDWI). For processing, the main data use is Landsat 8 OLI imagery which is downloaded from USGS website. The result shows that Band Ratio offer highest accuracy as compared to the other tested techniques.